The Influence of Textual and Contextual Understanding of Hadith on Tolerance and Interfaith Cooperation: Pengaruh Pemahaman Tekstual dan Kontekstual Hadis terhadap Toleransi dan Kerja Sama antar Agama - Moh. Misbakhul Khoir (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
The religious practices of Muslims consequence of the interpretive models they use present an interesting subject for study. The presence of both textual and contextual approaches has, to some extent, influenced differences in religious attitudes and behaviors. Therefore, this research seeks to identify the differences between textual and contextual models of understanding hadith and their influence on religious tolerance and interfaith cooperation. To begin the study, two research questions are posed: First, how do the attitudes toward religious tolerance compare between students with a textualist understanding and those with a contextualist understanding of hadith? Second, how do their attitudes toward cooperation differ in understanding hadith? These research questions are examined through quantitative research using a causal-comparative (ex post facto) method with a sample of second-semester students from the Faculty of Ushuluddin and Da'wah at IAIN Kediri. The research indicates that there is a significant difference between textual and contextual groups in terms of religious tolerance. The t-test results show a sig. (2-tailed) value of 0.000, smaller than 0.050, indicating a statistically significant difference. Likewise, in terms of cooperation attitude between the textual and contextual groups, the t-test results showed a sig. (2-tailed) of 0.000, which is smaller than 0.050, so the difference is quite significant.